2015
DOI: 10.1177/0960327115597980
|View full text |Cite
|
Sign up to set email alerts
|

Abrogated cardioprotective effect of ischemic preconditioning in ovariectomized rat heart

Abstract: Background: Ischemic heart disease is the leading cause of death in postmenopausal women. The expression of caveolin, a membrane protein and a negative regulator of nitric oxide (NO), increases after menopause. The present study was designed to determine the effect of daidzein (DDZ), a phytoestrogen in attenuated cardioprotective effect of ischemic preconditioning (IPC) in ovariectomized rat heart. Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…However, estrogen replacement or selective activation of PKCε-mediated signaling can fully restore the IPC effect, the translocation and phosphorylation of PKCε, and the phosphorylation of PDK1 [143]. It has been well documented by our laboratory that ovariectomy reduces the activity of eNOS in cardiac tissue due to upregulation of its inhibitory protein caveolin [144], but the chronic estrogen treatment accompanies restoration of normal activity of myocardial eNOS [145].…”
Section: Postmenopausementioning
confidence: 97%
“…However, estrogen replacement or selective activation of PKCε-mediated signaling can fully restore the IPC effect, the translocation and phosphorylation of PKCε, and the phosphorylation of PDK1 [143]. It has been well documented by our laboratory that ovariectomy reduces the activity of eNOS in cardiac tissue due to upregulation of its inhibitory protein caveolin [144], but the chronic estrogen treatment accompanies restoration of normal activity of myocardial eNOS [145].…”
Section: Postmenopausementioning
confidence: 97%
“…Current document is Daidzein restores the attenuated cardioprotective effect of IPC in ovariectomized rat heart, which may additionally be due to downregulation of caveolin that leads to elevated availability of NO and consequent increase in the activation of mitochondrial K ATP channels. The result show that perfusion of L-NAME, an eNOS inhibitor, and glibenclamide, a K ATP channel blocker, significantly attenuated the DDZ-induced cardioprotective impact of IPC in ovariectomized [83] and diabetic rat heart [13]. Gupta et al mentioned that activation of Heme oxygenase-1 via a specific activator, that is, hemin, restored the attenuated cardioprotective effect of IPC in diabetic rat heart by means of disrupting the caveolin-eNOS complicated and thereby enhancing the release of NO.…”
Section: Connection Of Ischaemic Preconditioning Through the Activitymentioning
confidence: 88%
“…However, aging tends to reduce the capability of the preconditioning stimuli to decrease the oxidative stress in the senescent hearts by decreasing the expression of antioxidant genes such as PGC-1α [ 15 ]. In addition, decrease in JAK-STAT-3 activity [ 98 ]; increase in MAP kinase phosphatase and decrease in MAP kinase expression; alteration in ionic balance (Na + and K + ) inside cardiomyocytes [ 29 ]; reduction in myocardial gap junction protein, connexin 43 content [ 28 ]; caveolin abundance and decrease in NO signaling [ 103 104 ] and increases phosphatase activity leading to decrease in phosphorylation of cell signaling proteins [ 106 ] may contribute in attenuating ischemic preconditioning-induced cardioprotection in senescent hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Ajmani and co-workers reported that ischemic preconditioning fails to provide cardioprotection in diabetic rat hearts possibly due to up-regulation of caveolin and subsequent, reduction in eNOS activity [ 103 ]. Similarly, another study has reported that ischemic preconditioning fails to provide cardioprotection in ovariectomized rats possibly due to up-regulation of caveolin and decline in eNOS activity [ 104 ]. Moreover, it is also documented that the levels of caveolin-1 and caveolin-3 are increased with aging in the cardiomyocytes [ 105 ].…”
Section: Mechanism Responsible For Reduced Effectiveness Of Differentmentioning
confidence: 99%